2014
DOI: 10.1016/j.jtcvs.2013.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre–stage II hemodynamics and pulmonary artery anatomy on 12-month outcomes in the Pediatric Heart Network Single Ventricle Reconstruction trial

Abstract: Objective To compare interstage cardiac catheterization hemodynamic and angiographic findings between shunt types for Single Ventricle Reconstruction (SVR) trial. Background The SVR trial, which randomized subjects to modified Blalock-Taussig shunt (MBTS) or right ventricle-to-pulmonary artery shunt (RVPAS) for the Norwood procedure, demonstrated RVPAS was associated with smaller pulmonary artery diameter, but superior 12-month transplant-free survival. Methods We analyzed pre-stage II catheterization data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
(28 reference statements)
1
26
0
2
Order By: Relevance
“…The modified Blalock–Taussig (MBT) shunt involves a connection between the innominate or subclavian artery and one of the branch pulmonary arteries. In some studies, the MBT shunt has been associated with haemodynamic instability [2] and sudden death [3] in the postoperative period. The right ventricle-to-pulmonary artery (RVPA) conduit was developed to offset this risk [4].…”
Section: Introductionmentioning
confidence: 99%
“…The modified Blalock–Taussig (MBT) shunt involves a connection between the innominate or subclavian artery and one of the branch pulmonary arteries. In some studies, the MBT shunt has been associated with haemodynamic instability [2] and sudden death [3] in the postoperative period. The right ventricle-to-pulmonary artery (RVPA) conduit was developed to offset this risk [4].…”
Section: Introductionmentioning
confidence: 99%
“…The size of the branch pulmonary arteries (BPAs) significantly influences the efficiency of the Fontan circulation [1,2]. Both central BPA stenosis and small left pulmonary artery (LPA) are known problems with the classical Norwood and its Sano modification [3,4]. Although this problem is documented since early reports, there is very little research into the factors influencing such problems [5].…”
Section: Introductionmentioning
confidence: 99%
“…10,27,28 Disproportionate left PA interventions would not have been predicted based upon the early results from the PHN Single-ventricle Reconstruction trial, which demonstrated a greater burden of right PA stenosis at the pre-BCPA catheterization. 29 Use of spontaneous ventilation was most common in the post-Fontan cohort, likely reflecting the increased age, size, and overall stability of this more mature cohort. Although the impact of assisted ventilation on acute postoperative hemodynamics has been assessed previously in stage II and Fontan palliated patients, [30][31][32] no prior reports have examined the relation of airway management to invasive hemodynamics in the setting of elective catheterization.…”
Section: Patients and Proceduresmentioning
confidence: 98%